Incident heart failure in outpatients with chronic coronary syndrome: results from the international prospective CLARIFY registry. (15th April 2020) - Parma, Zofia; Jasilek, Adam; Greenlaw, Nicola; Ferrari, Roberto; Ford, Ian; Fox, Kim; Tardif, Jean‐Claude; Tendera, Michal; Steg, P. Gabriel
Abstract: Aim: The contemporary incidence of heart failure (HF) in patients with chronic coronary syndrome is unclear. We aimed to study the incidence and predictors of cardiovascular (CV) death, HF hospitalization or new‐onset HF not requiring hospitalization, in patients included in the CLARIFY registry. Methods and results: CLARIFY is a contemporary, international registry of ambulatory patients with chronic coronary artery disease, conducted in 45 countries. At baseline, data on demographics, ethnicity, CV risk factors, medical history, cardiac parameters and medication were collected. Patients were followed up yearly up to 5 years. In this analysis, 26 769 patients with no HF history were included. At 5‐year follow‐up, 4393 patients (16.4%) reached the primary endpoint comprising CV death, HF hospitalization, or new‐onset HF. Only 16.7% of them ( n  = 732) required hospitalization for HF. All‐cause death occurred in 6.6% of patients (61.4% were CV). Age over 70 years, left ventricular ejection fraction <50%, Canadian Cardiovascular Society class ≥2 angina, atrial fibrillation or paced rhythm on the ECG, body mass index <20 kg/m 2, and a history of stroke, were the most robust predictors of the primary outcome. Age <50 years, Asian ethnicity, and percutaneous revascularization were negative predictors of the outcome. Conclusion: A sizeable proportion of patients with chronic coronary syndrome develop HF, which only infrequently requires hospitalization. Early identification of patients with HF may lead to early treatment, and help to further decrease mortality and morbidity. This concept needs confirmation in future studies.